Expansive Learning in Teacher Education's Hybrid Spaces: The Challenges and Possibilities in and Beyond Learning Studios - Imants, Jeroen; Meijer, Paulien C.; Blankesteijn, Erik (Frontiers in Education, 2020)
This article uses the concept of expansive learning from activity theory as a lens to understand learning in and beyond hybrid or third spaces in teacher education. In so-called “Learning Studios,” student teachers, experienced teachers and teacher educators learned through exploratory activities, leading to new insights, “familiarized knowledge” and expanded practices. However, while learning in Learning Studios was supposed to affect schools and universities (as activity systems), labeled as “snowballing,” this only occurred sporadically. Using expansive learning theory and its prominent role of contractions, we developed a better understanding of – and explanation for – the lack of snowballing. We developed suggestions for snowballing in schools and universities based on the successful characteristics of learning in Learning Studios.